A Summary Catechism in Arabic Abrégé de la doctrine chrétienne - Anonymous, Anonymous (Syriac Studies Library, 2012)
This volume presents a summary catechism in Arabic for young students and includes a number of prayers and an overview of Christian beliefs, duties, and means of sanctification